(NpOWY[ENIE \KSPLUATACIONNOJ NADEVNOSTI DETALEJ MA[IN (B/s - (NgROZIN b(B. (Nd(B.s; (NdRAJGOR d(B. (Na(B.s; (NsEMIROG(B-(NoRLIK w(B. (Nn(B.s ((NmOSKWA (B;s (NkIEW (B:s (NmA[GIZ(B,s, 1960)
[ (NpRIW(B. (NDANNYE O WLIQNII USLOWIJ TRENIQ I IZNOSA NA PREDEL USTALOSTI I OGRANI^ENNU@ WYNOSLIWOSTX STALI (B].s
(NbIBLIOGR(B.: (NS(B. 288 - 299 (40 (NNAZW(B.)s
Keywords: (N|KSPLUATACIONNAQ NADEVNOSTXs; (NdETALI MA[INs; (NtRENIEs; (NiZNOSs